Analysis of Medical Personnel Communication Competence Prof. Dr. Chairuddin Panusunan Lubis University of Sumatera Utara Hospital with Coronavirus Disease Patients Through the Use of Telemedicine in Medan - Permata, Adesima Qistee; Zulkarnain, Iskandar; Kurniawati, Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the communication competence of medical staff at Prof. Dr. Hairuddin Panusunan Lubis Hospital, Universitas Sumatera Utara, in interacting with COVID-19 patients through the utilization of telemedicine. The purpose of this research is to evaluate how effectively medical staff communicate with patients in a virtual environment, focusing on clarity, empathy, and professionalism. The research was conducted using a mixed-method approach, including surveys and interviews with both medical staff and patients. The results indicate that while telemedicine has facilitated continued care, there are significant challenges in maintaining effective communication. Recommendations for improving communication skills in telemedicine are discussed.